PANDANGAN FORUM KERUKUNAN UMAT BERAGAMA MENGENAI MAKNA TOLERANSI ANTARUMAT BERAGAMA DI JAWA BARAT - Latifah Latifah; Achwan Noorlistyo Adi; Adila Afifah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This study aims to analyse how West Java FKUB (Forum Kerukunan Umat Beragama)’s view on the meaning of tolerance relates to intolerance issue in West Java. The coverage on intolerance issue in mass media, escpecially about church construction that occurred in West Java becomes wide concern. The observations of non-governmental organizations in recent years showed West Java as the most intolerant province based on the increasing complaints of citizens related to intolerance. This research is qualitative research using case study method. In analysing the case, the researcher used interactionism symbolic theory. The results of this research found that West Java is one of the Provinces in Indonesia which has tolerant life philosophy and pious muslims in practicing Islamic religion. FKUB has an important role to solve the problems related to issues and cases of intolerance in West Java as a forum for interfaith dialogue.